동치미 분말을 이용한 스낵의 품질 특성 - 최진주(Jin Joo Choi); 박유리(Yoo Ri Park); 정장호(Chang-Ho Chung) (東아시아食生活學會誌, 2014)
Consumer's demand for higher dietary fiber and lower fat in processed foods are increasing. This study developed a low fat and high dietary fiber snack using egg whites and dry fermented radish powder obtained from Dongchimi fermentation. Quality characteristics, such as hardness, color, fat content and total dietary fiber, of the developed snack were conducted along with a hedonic test. As the amount of the fermented powder increased in the formulation, water content and snack hardness decreased. Up to 14.5% radish powder was added (or 9.54% dietary fiber; dry weight, w/w) to the formulation, and hedonic test found snack containing 4.8% (w/w) powder showed the highest scores for overall acceptability.